RELAXATION EFFECTS ON THE 3D PHOTOIONIZATION OF ATOMIC KRYPTON AND THE BROMINE NEGATIVE-ION - (:unkn) unknown (IOP PUBLISHING LTD, 1992)
A calculation for the photoionization parameters for the 3d shell of Kr and Br-is performed within the framework of the relativistic random-phase approximation including excitations from the 3d, 4s and 4p shells. The relaxation of the 3d subshell is included by using a set of relaxed one-electron orbitals in solving the random-phase approximation equations for both atomic systems and is found to be quite significant for the reproduction of the experiment. The total cross sections for Kr and Br- are found to display similar behaviour over a wide energy range starting from their thresholds. The results for Kr are compared with experimental data.
Keywords: RANDOM-PHASE APPROXIMATION; PHOTO-IONIZATION; RESONANCES; XENON